2015
DOI: 10.4102/jef.v8i1.94
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing risk-related disclosure in South Africa: a study on guidelines and current practices

Abstract: Investors partake in the risk of a company, in expectation of a return on investment which is in accordance with the company’s risk profile. Due to recent corporate failures, which are partly attributable to insufficient risk management, a call by investors for enhanced risk-related disclosure resulted in the publication of various international standards and guidelines on best practices for risk disclosure. This study compiled a disclosure index from these standards and guidelines in order to serve as a discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 17 publications
2
20
1
Order By: Relevance
“…Furthermore, one the most disclosed content elements is Principal Risks and Their Management, with a score of 0.90 (45 companies out of 50 report this item). Also, this value is higher than the values obtained in previous research [58,59] and can be read in light of the dissatisfaction shown by investors and stakeholders in recent years regarding several corporate scandals and failures, such as those of Enron, Worldcom, and Adelphia, with respect to the general level of risk and risk management disclosure provided by the companies [44,79,80]. Indeed, for investors and stakeholders, a higher level of risk disclosure allows for conducting a better assessment of the risk profile of a company by reducing the equity cost and improving the market efficiency [44,46,81].…”
Section: Compliance Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, one the most disclosed content elements is Principal Risks and Their Management, with a score of 0.90 (45 companies out of 50 report this item). Also, this value is higher than the values obtained in previous research [58,59] and can be read in light of the dissatisfaction shown by investors and stakeholders in recent years regarding several corporate scandals and failures, such as those of Enron, Worldcom, and Adelphia, with respect to the general level of risk and risk management disclosure provided by the companies [44,79,80]. Indeed, for investors and stakeholders, a higher level of risk disclosure allows for conducting a better assessment of the risk profile of a company by reducing the equity cost and improving the market efficiency [44,46,81].…”
Section: Compliance Analysismentioning
confidence: 62%
“…On the other hand, the Health Care sector shows the lowest average number of pages in a report with a mean of 217.5. As already noted, 204 pages should be enough to contain all the necessary information that an investor needs [79].…”
Section: Compliance Analysismentioning
confidence: 99%
“…Our findings support Beretta and Bozzolan (2004) and Oliveira et al (2011), who confirm the majority of disclosures are backward-looking. Forward-looking information is more relevant to stakeholders who wish to assess the future impact of the firm's risks as part of their decision-making process to invest (Beretta and Bozzolan, 2004;Abraham and Cox, 2007;Dobler, 2008;Rajab and Handley-Schachler, 2009;Enslin et al, 2015). Lower levels of forward-facing risk disclosure are also a signal that companies have only partially complied with the requirements set out in the <IRF>, which ask companies to provide information on future risks even in uncertain conditions (IIRC, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…With firm ownership concentrated in only a few families, the role of the stock market is limited visà-vis powerful banks in credit and financing (Alexander and Servalli, 2011;Jaggi et al, 2016). Listed Italian firms must produce financial statements according to the international accounting standards (IAS/IFRS), but none of these standards, beyond a 2010 IASB practice statement, require an accompanying management commentary (Haller and Van Staden, 2014;Enslin et al, 2015). The practice statement suggests the management commentary should include a description of the:…”
Section: Research Context Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation